Use of Bentonite Adsorbent from Ujong Pacu for the Adsorption Free Fatty Acids from Crude Palm Oil - Muhammad, Muhammad; Kamar, Iqbal; Chandra, Annisa Ramadhani; Shrestha, Ashish; Pandey, Govinda Prashad (Journal of Renewable Energy, Electrical, and Computer Engineering, 2023)
Because free fatty acid content impacts crude palm oil's physical and chemical characteristics, it is a good indicator of the oil's quality. Investigated effective operating parameters include contact time on adsorption and initial free fatty acid concentration. This system was studied using Langmuir and Freundlich isotherms, and the kinetic data was examined using pseudo-first-order and pseudo-second-order models. The findings indicated that increasing FFA concentrations increased the adsorption capacity of free fatty acids using Ujong Pacu bentonite, and it was discovered that CPO weighing 30 g was the ideal weight for FFA adsorption capacity. At equilibrium, the ideal value of adsorption capacity is 502.17 mg/g. While the pseudo-second order model is the model that best describes the adsorption kinetics of the free fatty acid content in Crude, the Freundlich isotherm model best describes the equilibrium data, which indicates the heterogeneous surface of the adsorbent pores and shows that the adsorbate layer formed on the surface of the adsorbent is multilayer. Correlation coefficient (R2) for palm oil (CPO) in the range of 0.946 to 0.9975.